Pengembangan Telegram Chatbot Informasi Mahasiswa Menggunakan Wit.ai - Joey Ferelestian, Varrel; Susanto, Budi; Senapartha, I Kadek Dendy (Fakultas Teknologi Informasi, 2023)
Messenger has become a medium that is widely used by humans to communicate and exchange information. Telegram is one of the most widely used Messengers. Telegram has a chatbot feature. Chatbot speeds up receiving information from websites to users. Receiving information through the website requires several steps to obtain information, while chatbots only need requests from users in the form of text. In this study, a Telegram chatbot will be created using Natural Language Processing (NLP) which focuses on several tasks such as Natural Language Understanding (NLU) and Natural Language Generation (NLG). The chatbot training will use the cloud vendor Wit.ai Natural Language Processing (NLP) service. The results of this study are chatbots trained using the Wit.ai NLP Service cloud vendor can process requests from users and provide responses to users according to previously requested information in a short time. The answers given by the chatbot have an accuracy rate above 0.6.